Anemia in female patients with myasthenia gravis - Sekiguchi, Koji; Ishizuchi, Kei; Takizawa, Tsubasa; Motegi, Haruhiko; Oyama, Munenori; Nakahara, Jin; Suzuki, Shigeaki (PLOS ONE, 2022)
Myasthenia gravis (MG) is the most common autoimmune neuromuscular disorder, and is more common in women than in men. Anemia is also more common in women. The purpose of this study was to investigate factors associated with anemia and the negative impact of anemia in female MG patients. We investigated factors related to MG and anemia in 215 female patients with MG, who were attending the MG clinic of Keio Hospital between January and December 2021. We statistically evaluated clinical factors related to anemia in patients with and without anemia. Eighty-five patients (40%) had anemia in the past, and 130 patients did not have anemia in the past. There were no significant differences in age at study, age at MG onset, body mass index, or frequency of autoantibodies between the anemia and non-anemia groups. MG severity evaluated by the MG Foundation of America classification was greater in the anemia group than in the non-anemia group. History of anemia was associated with immunosuppressive treatment, such as prednisolone and calcineurin inhibitor treatment. There was a correlation between hemoglobin levels and the MG-quality of life score. Long term immunosuppressive therapy can cause anemia in female MG patients. Anemia may negatively affect the quality of life of female MG patients.